Implementation of Community-Based Education in Increasing Learning Interest of Marginalized Children in School - Ahmad Zubaidi; Seroja Ainun Nadifah (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Marginalized communities, such as children in remote areas with various limitations in the economic, geographical and educational fields they face, all the limitations that cause underdevelopment, especially in the field of Education, these children lack enthusiasm for learning at school. This research was conducted at SDN Kalipenggung 04, Randuagung, Lumajang. This research aims to find out how the results of the implementation of Community-based Education Learning increase the enthusiasm for learning in schools so that schools with a mountainous geographical background and far from urban areas can achieve achievements, especially in the field of athletics or by the potential possessed by many students so that students can make maximum use of what they already have This research uses a qualitative approach of case study type using an explanatory analysis model. The results of this study show that implementing Community-based Education in increasing the enthusiasm for learning of marginalized children has proven to increase the interest of marginal children. This is evidenced by some of the achievements they have achieved both at the district and provincial levels.